Emotional intelligence and communication competence: the moderating roles of personality traits / Nur Athirah Sumardi - Sumardi, Nur Athirah (2018)
Communication is recognized as one of the important criteria in employment whereby, employers tend to look at the job candidates’ abilities in expressing themselves through their communication skills. The main purpose of this research was to investigate the moderating effects of personality traits towards the relationship between emotional intelligence and communication competence among final year undergraduate students in four public universities in Klang Valley. The four universities involved in this study were UM, UKM, UPM and UiTM. A correlational study design was applied for this study and data were collected by using quota sampling. Data were obtained through a set of questionnaires comprised of four sections. A pilot study was done prior to the actual data collection process, validating the instruments used. Exploratory Factor Analysis was conducted to establish the components under investigation. Besides, the researcher used descriptive, correlational, multiple regression, hierarchical regression analysis to analyze the data obtained. The findings of this study revealed that there was a relationship between emotional intelligence and communication competence among the final year students.